Dilema Muhammadiyah dalam Membantu Krisis Kemanusiaan Rohingya di Myanmar - Marha Fathu Masturah Adam; Surwandono Surwandono (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study analyzes the strategies employed by Muhammadiyah in addressing the humanitarian crisis affecting the Rohingya ethnic group in Myanmar, along with its positioning within international policy frameworks. A qualitative method was used, incorporating in-depth interviews with the chairman and vice chairman of the Muhammadiyah Disaster Management Center (MDMC), who served as key actors in aid distribution in Myanmar, along with three other representatives from Muhammadiyah’s leadership. Secondary data, including academic journals, news articles, online sources, and literature reviews, were also utilized to support the analysis. The findings reveal that Muhammadiyah faces various social, political, and cultural challenges in Myanmar, including local resistance, the politicization of aid, and language barriers. Unlike state-led humanitarian interventions, Muhammadiyah operates under regional diplomatic constraints. These conditions require adaptive negotiation strategies with both governmental and non-governmental stakeholders. This study highlights the critical role of faith-based organizations in humanitarian diplomacy and offers a comparative perspective on Muhammadiyah’s position alongside international actors such as UNHCR and ICRC. It emphasizes the need for cross-cultural communication training, integration with ASEAN’s humanitarian frameworks, and stronger institutional partnerships to improve the sustainability of humanitarian missions. Academically, this research contributes to the discourse on humanitarian diplomacy by exploring the intersection of religious-based humanitarianism and international political dynamics. Practically, it provides policy recommendations to enhance aid effectiveness in conflict-affected areas.